KONSEKUENSI NEGARA INDONESIA MENJADI ANGGOTA ICC (STUDI TENTANG MEKANISME PENEGAKAN HUKUM HUMANITER INTERNASIONAL) - Isplancius Ismail (Faculty of Law, Universitas Jenderal Soedirman, 2014)
International Humanitarian Law (IHL) is a set of rules which is based on the 1949 Geneva Law and Hague Law in 1907 and equipped with Additional Protocols I and II of 1977. IHL seeks to provide protection to the victims of war and civilians in armed conflict (law of Geneva 1949) and what methods and tools that may be used in war (Hague Law 1907). The parties involved in armed conflict must respect the principles of limitation, proportionality and distinction. Violations of international humanitarian law called war criminals must be prosecuted as crimes against human rights. Enforcement of international humanitarian law carried out through the mechanism according to the 1949 Geneva Law, by temporary or ad hoc Court, and by the International Criminal Court (ICC). The method used in this research is normative qualitative approach by taking secondary data as a source of information. The results indicate that the consequences of Indonesia as a state to be a member of ICC are having the synergy process national law with Rome Statute covering criminal law, criminal procedural law, extradition, human rights court and the law of human rights itself. The final goals of the synergy are to make Rome Statuta as a follow up system of national judicial, to avoid conflict between ICC and the law of Indonesia, and to make internal law procedure for Indonesia when ICC jurisdiction is active in Indonesia Key words: humanitarian law, war criminal, court jurisdiction